Potential of Moringa oleifera (M. oleifera) Leaf Extract as an Antiseptic against Candida albicans using Percentage Kill Test - Tjampakasari, Conny Riana; Kiranasari, Aryani; Baswara, R. Muh. Kevin (Majalah Obat Tradisional, 2025)
Candida albicans is a commensal microorganism that is commonly found as a normal flora in the body. However, impaired immune conditions can cause this fungus to turn into a pathogen. This Microorganism is one of the causes of mortality and morbidity in the world. The use of antiseptics is beneficial for the prevention and treatment of fungal infections. Moringa oleifera is a plant that is often found in Asia and Africa, has various bioactive components that have the potential to be antiseptic. Until now, there has been no research on the antiseptic potential of M. oleifera against C. albicans. Therefore the study was conducted to test the activity of Moringa leaf extract (Moringa oleifera) as an antiseptic against C. albicans. This experiment was conducted using the percentage kill method to determine the potential activity of the extract as an antiseptic against C. albicans The comparison of bacterial colony growth on the control and the treatment that grew on solid media was calculated according to the set contact time of 1, 2, and 5 minutes. The effectiveness of antiseptics is assessed by calculating according to the percentage kill principle. The results of the calculation of C. albicans colonies in contact time for 1, 2, and 5 minutes were 62.39%, 80.85%, and 90%, respectively. This finding shows that the contact time of 5 minutes has good effectiveness. Therefore M. oleifera leaves have the potential to be an effective antiseptic against C. albicans.